Predictors of radiation-induced late rectal toxicity in prostate cancer treatment: a volumetric and dosimetric analysis - Spohn, Simon K. B.; Radicioni, Gianluca; Eisfelder, Marcio; Zamboglou, Constantinos; Baltas, Dimos; Grosu, Anca-Ligia; Sachpazidis, Ilias (Frontiers in Oncology, 2024)
Introduction: Prostate cancer (PCa) is a prevalent malignancy in European men, often treated with radiotherapy (RT) for localized disease. While modern RT achieves high success rates, concerns about late gastrointestinal (GI) toxicities persist. This retrospective study aims to identify predictors for late GI toxicities following definitive conventionally fractionated external beam RT (EBRT) for PCa, specifically exploring the dose to the rectal wall. Materials and Methods: A cohort of 96 intermediate to high-risk PCa patients underwent EBRT between 2008 and 2016. Rectum and rectum wall contours were delineated, and 3D dose matrices were extracted. Volumetric and dosimetric indices were computed, and statistical analyses were performed to identify predictors using the Mann-Whitney U-rank test, logistic regression, and recursive feature elimination. Results: In our cohort, 15 out of 96 patients experienced grade II late proctitis. Our analysis reveals distinct optimal predictors for rectum and rectum wall (RW) structures, varying with α/β values (3.0 Gy and 2.3 Gy) across prescribed doses of 68 Gy to 76 Gy. Despite variability, RW predictors demonstrate greater consistency, notably V68Gy[%] to V74Gy[%] for α/β 3.0 Gy, and V68Gy[%] to V70Gy[%] for α/β 2.3 Gy. The model with α/β 2.3 Gy, featuring RW volume receiving 70 Gy (V70Gy[%]), stands out with a BIC value of 62.92, indicating its superior predictive effectiveness. Finally, focusing solely on rectum structure the V74Gy[%] emerges the best predictor for α/β 3.0 Gy, with BIC value of 66.73.Conclusion: This investigation highlights the critical role of V70Gy[%] in the rectum wall as a robust predictor for grade II late gastrointestinal (GI) toxicity following external beam radiation therapy (EBRT) for prostate cancer (PCa). Furthermore, our findings suggest that focusing on the rectum wall specifically, rather than the entire rectum, may offer improved accuracy in assessing proctitis development. A V70Gy (in EQD2 with α/β 2.3 Gy) of £5% and if possible £1% for the rectal wall should be achieved in order to minimize the risk of late grade II proctitis.